Assessing Modeled CO2 Retention and Rebreathing of a Facemask Designed for Efficient Delivery of Aerosols to Infants. (26th June 2012) - Mundt, Christian; Sventitskiy, Alexander; Cehelsky, Jeffrey E.; Patters, Andrea B.; Tservistas, Markus; Hahn, Michael C.; Juhl, Gerd; DeVincenzo, John P.
Abstract : Background . New aerosol drugs for infants may require more efficient delivery systems, including face masks. Maximizing delivery efficiency requires tight-fitting masks with minimal internal mask volumes, which could cause carbon dioxide (CO2 ) retention. An RNA-interference-based antiviral for treatment of respiratory syncytial virus in populations that may include young children is designed for aerosol administration. CO2 accumulation within inhalation face masks has not been evaluated. Methods . We simulated airflow and CO2 concentrations accumulating over time within a new facemask designed for infants and young children (PARI SMARTMASK ® Baby). A one-dimensional model was first examined, followed by 3-dimensional unsteady computational fluid dynamics analyses. Normal infant breathing patterns and respiratory distress were simulated. Results . The maximum average modeled CO2 concentration within the mask reached steady state (3.2% and 3% for normal and distressed breathing patterns resp.) after approximately the 5th respiratory cycle. After steady state, the mean CO2 concentration inspired into the nostril was 2.24% and 2.26% for normal and distressed breathing patterns, respectively. Conclusion . The mask is predicted to cause minimal CO2 retention and rebreathing. Infants with normal and distressed breathing should tolerate the mask intermittently delivering aerosols over brief time frames.